Like a Natural Woman : Spectacular Female Performance in Classical Hollywood - Pullen, Kirsten (Book collections on Project MUSE., 2014)
"Bathing beauty Esther Williams, bombshell Jane Russell, exotic Carmen Miranda, chanteuse Lena Horne, and talk-show fixture Zsa Zsa Gabor are rarely hailed as great actors or as naturalistic performers. Those terms of praise are given to male stars like Marlon Brando and James Dean, whose gritty dramas are seen as a departure from the glossy spectacles in which these stars appeared. Like a Natural Woman challenges those assumptions, revealing the skill and training that went into the work of these five actresses, who employed naturalistic performance techniques, both onscreen and off. Bringing a fresh perspective to film history through the lens of performance studies, Kirsten Pullen explores the ways in which these actresses, who always appeared to be "playing themselves," responded to the naturalist notion that actors should create authentic characters by drawing from their own lives. At the same time, she examines how Hollywood presented these female stars as sex objects, focusing on their spectacular bodies at the expense of believable characterization or narratives. Pullen not only helps us appreciate what talented actresses these five women actually were, but also reveals how they sought to express themselves and maintain agency, even while meeting the demands of their directors, studios, families, and fans to perform certain feminine roles. Drawing from a rich collection of classic films, publicity materials, and studio archives, Like a Natural Woman lets us take a new look at both Hollywood acting techniques and the performance of femininity itself"--